2008
DOI: 10.1002/bdd.638
|View full text |Cite
|
Sign up to set email alerts
|

Plasma pharmacokinetics and tissue distribution of [6]‐gingerol in rats

Abstract: [6]-Gingerol is one of the pungent components in ginger which has been found to possess various pharmacological effects. However, there is insufficient information on the properties of [6]-gingerol based on controlled pharmacokinetic studies. The aim of this study was to clarify distribution profiles of [6]-gingerol in blood and biological tissues of experimental rats. Rats were administered a 240 mg/kg dose of Gs (a ginger extract, containing 53% [6]-gingerol) by oral ingestion. Plasma samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 9 publications
3
60
1
1
Order By: Relevance
“…However, the peak concentrations determined for 10-gingerol and 6-shogaol were 9.5±2.2 ng/mL (0.027±0.006 μM) and 13.6±6.9 ng/mL (0.049±0.025 μM), which were less than the IC 50 's of 10-gingerol and 6-shogaol (12 and 8 μM, respectively). Although gingerols and shogaol might be higher in colon tissues (31), in the present study, only limited amounts of 10-gingerol glucuronide and sulfate conjugates were detected at 24 h after multiple daily dosing. To better understand the pharmacokinetics of gingerols and shogaol in colon tissues and correlate the pharmacokinetic to pharmacodynamic effect, early sampling time would be required to quantify the drug concentrations in colon tissues in future clinical studies.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…However, the peak concentrations determined for 10-gingerol and 6-shogaol were 9.5±2.2 ng/mL (0.027±0.006 μM) and 13.6±6.9 ng/mL (0.049±0.025 μM), which were less than the IC 50 's of 10-gingerol and 6-shogaol (12 and 8 μM, respectively). Although gingerols and shogaol might be higher in colon tissues (31), in the present study, only limited amounts of 10-gingerol glucuronide and sulfate conjugates were detected at 24 h after multiple daily dosing. To better understand the pharmacokinetics of gingerols and shogaol in colon tissues and correlate the pharmacokinetic to pharmacodynamic effect, early sampling time would be required to quantify the drug concentrations in colon tissues in future clinical studies.…”
Section: Discussioncontrasting
confidence: 68%
“…These data demonstrated no accumulation of 6-, 8-, and 10-gingerols and 6-shogaol or their conjugate metabolites in plasma after 24 days of multiple daily dosing regimens due to their short half-lives and fast clearance. (31), no free 6-gingerol and its metabolites were detected in the colon tissues at 24 h after multiple daily dose ginger powder capsules. Only marginal levels of 10-gingerol glucuronide and sulfate conjugates were detected at 24 h after multiple daily doses of ginger powder capsules which ranged from 1.72 to 2.76 ng/mL.…”
Section: Concentrations Of 6- 8- and 10-gingerols And 6-shogaol Andmentioning
confidence: 86%
“…These findings corroborate the results of a previous study in which a maximal concentration of [6]-gingerol in rat plasma was reached within 10 min after oral administration (Jiang et al, 2008). On the other hand, Zick et al (2008) reported that no free [6]-gingerol, [8]-gingerol, [10]-gingerol, or [6]-shogaol was found, but instead their conjugates were detected in human plasma after oral dosing of ginger extract capsules.…”
Section: Discussionsupporting
confidence: 90%
“…There are reports on analyses of plasma profiles of metabolites after oral dosing of ginger and ginseng (Yan et al, 2007;Jiang et al, 2008;Lee et al, 2009). However, no study on ADME of zanthoxylum fruit, as a single herb or as a part of a combination drug, has been reported to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Under physiological conditions, orally administered [6]-gingerol is absorbed through the intestinal mucosa and transferred to the serosal side. Jiang et al reported that the maximal plasma concentration of [6]-gingerol was reached 10 min after oral administration (22), suggesting that [6]-gingerol is mostly absorbed in the small intestine rather than in the colon. The serosal side of the colon possesses the enteric nervous system and blood vessel.…”
Section: /Hco3mentioning
confidence: 99%